The land before time VII : the stone of cold fire (Universal City, Calif : Universal Home Video, 2002)
Little foot has witnessed an amazing sight: a stone of cold fire that fell through the night sky and landed somewhere in the Smoking Mountains. But Little foot is the only one in the Great Valley who saw the stone and he can't find anyone who believes him.